INFLUENCE OF BILE ON LACTOBACILLI VIABILITY AND ABILITY TO REDUCE LACTOSE IN MRSL BROTH - Utami, Tyas; Kasmiati, Kasmiati; Harmayani, Eni; Rahayu, Endang Sutriswati (2009)
Lactobacillus bulgaricus (yogurt starter), Lactobacillus acidophilus N2 (isolated from fecal material), and lactobacillus sp Dad 13 (isolated from dadih, a west sumatera traditional feremented buffalo milk)were investigated for prroperties relevant to the production of fermented milk products for consumption by lactose-intolerant humans. In vitro Assesment of acid tolerance ofd lactobacilli was carried out in MRSL at pH values of 2.0, 2.5, 3.0 and 3.5. The three lactobacilli were tested their bile sensitivity in MRSL broth containing 5% lactose, supplemented with various various concentration oxgall and evaluated their ability to reduce lactose content. There was relativity no loss of viability for all strains at pH 3.0 and 3.5, while at pH 2.0 they showed reduced viability for 2-3 log cycles after three hours of incubation. All three lactobacilli can grow in MRSL containing 0.5% oxgall, although their grow more slowly than in the absence of oxgall. Their viability tend to decrease with increase in oxgall concentration. The ability of three lactobacilli to reduce lactose content in MRSL higher in the presence of oxgall and tend to increase with the increase in oxgall concentration. The presence of 0.5 to 5% oxgall did not enhance of lysis of cells. It could be that the permeability of lactobacilli cells increased in the presence of bile, permitting more lactose substrate to enter the cells, thus increase their ability to reduce lactose in the media.